Provenance and Characterization of Pliocene Southern Ocean Sediment in Weddell Sea, Antarctica: Implications for Paleoclimatic Change - Gross, Jason Lewis; O'Connell, Suzanne (Suzanne B.) (2015)
With the advent of rapid anthropogenic global climate change and sea level rise, the stability of high latitude ice sheets is being increasingly scrutinized. An historical perspective of their stability is possible through analysis of marine sediment cores, which provide a record of glacial dynamics. More information about the Pliocene, when atmospheric CO 2 were as high as today, can be used to better understand the consequences of changes in climate. This study focuses on the Antarctic continental slope by analyzing deep-sea cores of Early Pliocene age, taken from the margin of the East Antarctica Ice Sheet (EAIS) at ODP Site 693. The study area is adjacent to a region that modeling simulations suggest experienced stable periods of warmth compared to the rest of the continent (Pollard et al., 2015). The coarse grain fraction of ODP Site 693 sediment samples was interpreted as material deposited by ice-rafting (IRD). The weight percent of IRD was compared to XRF-derived elemental concentrations (oxide weight percent), biogenic silica abundance, and changes in mineralogy to illuminate paleoenvironmental conditions. Few peaks in IRD were correlated with increases in Ca, Fe and Ti. Biosilica abundance displayed a positive association with K/Ti ratios. 40 Ar/ 39 Ar radiometric dating revealed the majority of hornblendes and biotite grains to be of Pan-African age (650-480 Ma), which does not reflect nearby Archaean geology, and contrasts age populations from core samples from nearby sites. This fact combined with unchanging heavy mineral assemblages downcore suggests a singular source during Core 8R, and stable behavior for the EAIS.